2014
DOI: 10.1103/physrevb.90.134312
|View full text |Cite
|
Sign up to set email alerts
|

Role of anharmonic phonon scattering in the spectrally decomposed thermal conductance at planar interfaces

Abstract: A detailed understanding of the vibrational heat transfer mechanisms between solids is essential for the efficient thermal engineering and control of nanomaterials. We investigate the frequency dependence of anharmonic scattering and interfacial thermal conduction between two acoustically mismatched solids in planar contact by calculating the spectral decomposition of the heat current flowing through an interface between two materials. The calculations are based on analyzing the correlations of atomic vibratio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
229
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 262 publications
(248 citation statements)
references
References 42 publications
16
229
2
1
Order By: Relevance
“…The nonequilibrium heat current can be further decomposed for different frequencies, as recently demonstrated by Sääskilahti et al [31,32]. Here, we extend their method to include the in-out decomposition.…”
Section: Spectral Decompositionmentioning
confidence: 97%
See 3 more Smart Citations
“…The nonequilibrium heat current can be further decomposed for different frequencies, as recently demonstrated by Sääskilahti et al [31,32]. Here, we extend their method to include the in-out decomposition.…”
Section: Spectral Decompositionmentioning
confidence: 97%
“…We note that Sääskilahti et al [32] and Gill-Comeau and Lewis [34] have also demonstrated that applying the harmonic approximation in the calculation of the microscopic heat current barely affects the results. This is due to the small anharmonicity of the graphene lattice but cannot be guaranteed for other cases [31].…”
Section: Appendix A: Steady Statementioning
confidence: 99%
See 2 more Smart Citations
“…The role of anharmonicity of oscillations in the phonon transmission across the interface is considered in the paper [15]. In the most recent study [16], it has been found that atoms at the interface oscillate with a frequency exceeding the maximum possible frequency in a given crystal.…”
Section: Introductionmentioning
confidence: 99%